2009
DOI: 10.1038/nprot.2009.198
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous culture of Plasmodium falciparum at high parasitemia levels

Abstract: This protocol describes a method for preparing cultures of Plasmodium falciparum synchronized at any intraerythrocytic stage. Using this method, around 60% parasitized cells may be obtained. On the basis of Trager and Jensen's original continuous culture method, our approach relies on the use of fresh human blood not older than 2 weeks, a low hematocrit between 0.8 and 1.5%, a starting frozen inoculum of 10% ring-stage parasitemia, human serum replaced with AlbuMAX I and alternating sorbitol and Percoll synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
167
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 41 publications
1
167
0
Order By: Relevance
“…The cells were washed once with cell culture medium to remove the sorbitol, diluted to 5 vol% hematocrit with cell culture medium and further cultivated as described in the preceding texts. Schizont‐iRBCs were purified using Percoll gradient centrifugation as described (Radfar et al , 2009). To gain access to live MZ, schizont‐iRBCs were either treated with 0.05% saponin in incomplete cell culture medium (without serum) for 5 min at 37°C or the MZ were purified using a published protocol (Boyle et al , 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were washed once with cell culture medium to remove the sorbitol, diluted to 5 vol% hematocrit with cell culture medium and further cultivated as described in the preceding texts. Schizont‐iRBCs were purified using Percoll gradient centrifugation as described (Radfar et al , 2009). To gain access to live MZ, schizont‐iRBCs were either treated with 0.05% saponin in incomplete cell culture medium (without serum) for 5 min at 37°C or the MZ were purified using a published protocol (Boyle et al , 2010).…”
Section: Methodsmentioning
confidence: 99%
“…(−)epi-marmelo lactone (1) Biological screenings: Antimalarial screening: A primary screening for compounds 1-9 was done as per standard protocols [18] at the 10 µM concentration, and for the crude mixture, a 1 µg/mL concentration was used. Protocol details are given in Supporting Information.…”
mentioning
confidence: 99%
“…This method may be used to synchronize cultures for months, thus ensuring survival and a high degree of synchrony of parasites. As compared to other methods described using low hematocrit conditions [15], which are labor-intensive (requiring culture medium changes at any time for at least two weeks), our optimized method is simple to develop, maintains culture synchrony, and avoids stress to the parasites. This procedure (SorbitolPlasmion-Sorbitol) may be repeated every week taking into account the observations in Table 1, achieving a highly synchronous culture.…”
Section: Sorbitol 6 Hoursmentioning
confidence: 99%
“…It is very important to consider the maturity of trophozoite stages and, even more, the presence of early schizonts (two or three nuclei) when Plasmion treatment is applied, because the greater degree of maturity of trophozoites and even more schizonts may influence determination of the "0-hour start time" (95% of early rings obtained), which will be earlier when these stages (trophozoites and schizonts) are very mature. Another advantage of Plasmion treatment is that early and late schizonts are obtained without the need to combine a percoll gradient with sorbitol treatment [15]. Some authors [10] [15] recently reported a new synchronization method based on the combination of sorbitol treatment with percoll gradients and magnetic column purification to achieve high parasitemia levels (up to 40%).…”
Section: Sorbitol 6 Hoursmentioning
confidence: 99%